As an EU Education Programme, the Effect of Erasmus Exchange Mobility on Intercultural Communication and Language Learning: Array - Çankaya Kurnaz, Seda (Acta Universitatis Danubius. Communicatio, 2020)
Erasmus Programme is one of the European student exchange programmes established in 1987. This programme provides students the opportunity of studying and internship and also staff can teach or train in different European and Programme Countries through the programme. Since 1987, the number of students and staff participating in the programme has been growing. In this study, the impact of Erasmus program on outgoing students in terms of intercultural communication and language learning will be evaluated. As a method, qualitative research method is used and data are obtained by applying semi-structured interview technique. Descriptive method was used to analyze research data. A Number of questions were asked to the students of Selcuk University who went to Polish Institutions within framework of Erasmus Exchange Programme in order to evaluate the impact of the programme. The dimension of the foreign students' communication with each other will be tried to be determined through the questions of the study. The results of the study show that Erasmus Exchange Programme is successful to provide opportunities for intercultural encounters and increases the effect of language learning.